System Analysis of a Prawn Freezing Plant - I. Analysis of Raw Prawn Preparation and Freezing Operations - N., Kannan; S., Bandyopadhyay (Fishery Technology, 2025)
A system analysis approach has been taken to study and analyse various operations of a hypothetical prawn freezing plant. Results of analysis for processing three different products showed that the data on rate of prawn handling by a number of workers can be fitted to linear relations, and optimum operating conditions can be arrived at with minimum freezer idle time and maximum number of loads per freezer. lt has been further found that scheduling of prawn preparation time is very crucial during the early stage of processing.